2013
DOI: 10.26719/2013.19.10.876
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of intimate-partner violence and contraception use among ever-married women in Jordan

Abstract: This study explored the relationship between intimate partner violence (IPV) and current contraception use among ever-married women in Jordan. Analysing a sample (n = 3434) from the 2007 Jordan demographic and health survey, women who reported ever experiencing severe physical violence from their husband were significantly less likely to use contraception than women who did not report severe physical violence (OR = 0.34). Conversely, women who reported ever experiencing sexual IPV were significantly more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 19 publications
5
19
1
2
Order By: Relevance
“…This study shows that child desire was negatively associated with use of modern contraceptive. This finding is similar to previous studies [2] [7] [16]- [18]. In the present study when husbands want more children, women were less likely to use contraceptives compared with when couples wants the same number of children.…”
Section: Comparison To Other Studiessupporting
confidence: 92%
See 2 more Smart Citations
“…This study shows that child desire was negatively associated with use of modern contraceptive. This finding is similar to previous studies [2] [7] [16]- [18]. In the present study when husbands want more children, women were less likely to use contraceptives compared with when couples wants the same number of children.…”
Section: Comparison To Other Studiessupporting
confidence: 92%
“…Contraceptive use could be the source of conflict among couples, to escape from such harassment women are likely to withdraw from using contraceptive use to allow men's interest to prevail within the family. Similar in a study done by Dalal [8] and his colleagues found that sexual violence was not an important predictor for modern contraceptive use, contrary to a study done in Jordan by Montes, O'Hara and their colleagues [18] [22] found the odds of currently using contraception were greater for women who reported experiencing sexual violence compared those who did not. IPV could be associated with use of modern contraceptive among married/cohabiting women as means of protection for future problems especially unwanted pregnancy in case of sexual violence.…”
Section: Comparison To Other Studiesmentioning
confidence: 57%
See 1 more Smart Citation
“…Intimate partner violence (IPV) is a recognized global health problem with a 37% prevalence for the Eastern Mediterranean region (World Health Organization, 2013). In Jordan, a Middle Eastern country, IPV prevalence is 30% (O'Hara et al 2013), lower than the regional mean but still clinically significant. There is compelling research evidence that women who have experienced IPV are at high risk for immediate and long-term psychosocial depression, low level of perceived social support and poor physical health consequences (Lacey et al 2013;Hamdan-Mansour et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Studies of consanguinity in the Arab region suggest that consanguinity may be viewed more positively by men compared to women28 and be more common among individuals of lower socioeconomic status and individuals living in rural areas 11 29. In Jordan, consanguinity appears to have the additional benefits of reducing women's risk of experiencing interference in their ability to use contraception7 and appears to be protective against IPV;30 but has been associated with poor reproductive health outcomes such as preterm delivery and congenital malformations,29 31 and a reduced likelihood of using modern contraceptive methods 32. Polygyny, while not commonly practised, often places co-wives in competition.…”
Section: Introductionmentioning
confidence: 99%